Multiplicative reasoning: An intervention's impact on Foundation Phase learners' understanding - Askew, M.; Venkatakrishnan, H.; Mathews, C.; Ramsingh, T.T.; Roberts, N. (2019)
BACKGROUND: Given the context of low attainment in primary mathematics in South Africa, improving learners' understanding of multiplicative reasoning is important as it underpins much of later mathematics. AIM: Within a broader research programme aiming to improve Foundation Phase (Grades 1-3, 7-9-year-olds) learners' mathematical performance, the aim of the particular research reported on here was to improve learners' understanding of and attainment in multiplicative reasoning when solving context-based problems. SETTING: The research was conducted in a suburban school serving a predominantly historically disadvantaged learner population, and involved teachers and learners from three classes in each of Grades 1-3. METHODS: A 4-week intervention piloted the use of context-based problems and array images to encourage learners to model (through pictures and diagrams) the problem situations, with the models produced used both to support problem solving and to support understanding of the multiplicative structures of the contexts. RESULTS: Cleaning the data to include those learners participating at all three data points - pre-, post- and delayed post-test - provided findings based on 233 matched learners. These findings show that, on average, Grade 1 learners had a mean score average increase of 22 percentage points between the pre-test and the delayed post-test, with Grades 2 and 3 having mean increases of 10 and 9 percentage points, respectively. CONCLUSION: The findings of this study demonstrate that young learners can be helped to better understand and improve their attainment in multiplicative reasoning, and suggest the usefulness of trialling the intervention model more broadly across schools.
Keywords: Foundation Phase; multiplicative reasoning; assessment; raising standards